2023
DOI: 10.1101/2023.01.30.526213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The E3 ubiquitin ligase DTX3L and the deubiquitinase USP28 fine-tune DNA double strand repair through mutual regulation of their protein levels

Abstract: The DNA damage response involves a complex protein network with members mediating different post-translational modifications such as ubiquitination and deubiquitination. Thereby the E3 ubiquitin ligase DTX3L as well as the deubiquitinase USP28 are recruited especially to DNA double strand breaks (DSBs) suggesting mutual functional interactions. Here we present evidence for the existence of such crosstalk. Mechanistically we show that DTX3L interacts directly with USP28 and ubiquitinates it, which leads to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…As a final confirmation that the assay was able to detect inhibition of USP28, we measured the IC 50 value of a known dual inhibitor for USP28 and USP25 (AZ1) using the FRET-based assay ( Figure 4E ). We previously showed that in cells this compound is able to affect DTX3L in a similar fashion as knock down of USP28 (Ashok et al ., 2023) and the IC 50 value determined with our method (IC 50 = 8 μM) is close to the binding affinity (K d value of 3.7 μM) measured previously with microscale thermophoresis (MST) (Wrigley et al ., 2017). This indicates that our system can be adopted to identify and characterize inhibitors also for the DUB.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…As a final confirmation that the assay was able to detect inhibition of USP28, we measured the IC 50 value of a known dual inhibitor for USP28 and USP25 (AZ1) using the FRET-based assay ( Figure 4E ). We previously showed that in cells this compound is able to affect DTX3L in a similar fashion as knock down of USP28 (Ashok et al ., 2023) and the IC 50 value determined with our method (IC 50 = 8 μM) is close to the binding affinity (K d value of 3.7 μM) measured previously with microscale thermophoresis (MST) (Wrigley et al ., 2017). This indicates that our system can be adopted to identify and characterize inhibitors also for the DUB.…”
Section: Resultsmentioning
confidence: 90%
“…We have previously reported that there is a mutual regulation between USP28 and DTX3L in which the DUB hydrolyses poly-Ub chains generated by DTX3L. Ubiquitination of USP28 by DTX3L was also demonstrated with a catalytically inactive USP28 C171A mutant (Ashok et al, 2023). We therefore sought to test if addition of USP28 to pre-formed poly-Ub chains on DTX3L would lead to reduction in rFRET due to hydrolysis poly-Ub chains.…”
Section: Detection Of the Poly-ub Chains Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation